AIEgen based poly(L-lactic-co-glycolic acid) magnetic nanoparticles to localize cytokine VEGF for early cancer diagnosis and photothermal therapy. (26th March 2019) - Ma, Ke; Liu, Guo-Jun; Yan, Lulin; Wen, Shihui; Xu, Bin; Tian, Wenjing; Goldys, Ewa M; Liu, Guozhen
Aim: We demonstrated a novel theranostic system for simultaneous photothermal therapy and magnetic resonance imaging applicable to early diagnostics and treatment of cancer cells.Materials & methods: Oleic acid-Fe3 O4 and triphenylamine-divinylanthracene-dicyano were loaded to the poly(L-lactic-co-glycolic acid) nanoparticles (NPs) on which anti-VEGF antibodies were modified to form anti-VEGF/OA-Fe3 O4 /triphenylamine-divinylanthracene-dicyano@poly(L-lactic-co-glycolic acid) NPs. The 1H nuclear magnetic resonance (NMR), mass spectra, fluorescence, UV absorption, dynamic light scattering, transmission electron microscope and inductively coupled plasma mass spectrometry tests were used to characterize the NPs, and the bioimaging was illustrated by confocal laser scanning microscope (CLSM) and in vivo MRI animal experiment.Results: This system was capable to recognize the overexpressed VEGF-A as low as 68 pg/ml in different cell lines with good selectivity and photothermal therapy effect.Conclusion: These ultrasensitive theranostic NPs were able to identify tumor cells by fluorescence imaging and MRI, and destroy tumors under near infrared illumination.